The art of Marvel Studios What if ... ? Volume one - Davies, Paul (Game journalist) (Abrams, 2024)
"The Art of Marvel Studios' What If...? takes fans behind the scenes of Marvel Studios' first animated series...Through interviews with the animators, designers, producers, and writers of the series, readers will discover everything that goes into translating their favorite heroes and villains from live action to animation and how exciting new possibilities can open up if you only ask "What if...?""--adapted from dust jacket.